The importance of obligatoriness to demand the right to education in Mexico - Benavides-Lara, Mario Alberto (2020)
The present text offers a conceptual analysis about the implications of the Mexican legislation framework as a tool of obligatoriness to advance education as a right.  The central argument of the article is that obligatoriness, beyond being a normative postulate, is a mechanism that allows the enforceability of the right to education, which responds to a specific socio-political context.  However, the way in which the Mexican state has met this demand requires a new level of reflection in which the pedagogical proposals that are to emerge, be committed to be committed with the recognition of difference and diversity that currently seems to be absent.